The stick-around cloud - Vaughan, Marcia (Nelson Australia South Melbourne, Vic., 1994)
The Spoilt Holiday is a children$1 (Bs story about a much-anticipated vacation that takes an unexpected turn. The protagonist, a young child excited for a perfect holiday, faces a series of disappointments when things don't go as planned. From bad weather to missed activities, the holiday seems to be ruined at first. However, as the story unfolds, the protagonist learns to adapt and find joy in unexpected places, discovering that a good attitude and resilience can turn even a spoilt holiday into a memorable and meaningful experience. The story emphasizes themes of adaptability, gratitude, and making the best of challenging situations.s